2017
DOI: 10.1080/14767058.2017.1344209
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial content and hepcidin are increased in obese pregnant mothers

Abstract: Our results indicate a potential compensatory mechanism to increased obesity-related OxS and inflammation, indicated by the higher hepcidin levels found in obese mothers. Increased placental mitochondrial biogenesis, due to lipotoxic environment, may account for the greater mtDNA amount released in maternal circulation. This increase is namely related to F-carrying pregnancies, suggesting a gender-specific placental response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
3
23
1
3
Order By: Relevance
“…Few studies have evaluated the influence of obesity on hepcidin and iron status during pregnancy, but their results are inconclusive. While increased hepcidin in obese pregnant women was shown in previous studies,7 9 22 23 it has not been confirmed in another studies 25 26. Due to previous data, we expect to observe an increase in the serum hepcidin in obese pregnant women, consequentially increased soluble transferrin receptors as a marker for iron deficiency in cells and a lower level of Hb because of iron deficiency.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Few studies have evaluated the influence of obesity on hepcidin and iron status during pregnancy, but their results are inconclusive. While increased hepcidin in obese pregnant women was shown in previous studies,7 9 22 23 it has not been confirmed in another studies 25 26. Due to previous data, we expect to observe an increase in the serum hepcidin in obese pregnant women, consequentially increased soluble transferrin receptors as a marker for iron deficiency in cells and a lower level of Hb because of iron deficiency.…”
Section: Discussionmentioning
confidence: 63%
“…Obesity is a low-grade chronic inflammatory condition linked to the overexpression of hepcidin and secondarily to iron homeostasis. Increased hepcidin in obese pregnant women without GDM was shown in previous studies 7 9 22 23. Obesity-related inflammation may induce hepcidin biosynthesis with a consequent reduction of iron supply 7 24.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Similarly, in pregnancies complicated by pre-existing diabetes, suppressed placental mitochondrial respiratory chain enzyme activity has been shown 40. Interestingly, in obese women without GDM, contrasting findings such as heightened mtDNA content in the placenta28 and peripheral blood,41 suggesting increased mitochondrial biogenesis, have been reported. Collectively, these data point toward reduced placental mitochondrial biogenesis and/or respiratory capacity in diabetic pregnancies.…”
Section: Discussionmentioning
confidence: 99%